Pertanggungjawaban Hukum Pelaku Usaha Skincare Terhadap Kerugian Konsumen Akibat Overclaim Produk - Ni Kadek Vina Yuniardhi; Ni Luh Gede Yogi Arthani (Fakultas Hukum, Universitas Mahasaraswati Denpasar, 2026)
The progress of the Indonesian skincare industry has brought constructive implications for the public community, but has also given rise to problems in the form of competition without integrity and excessive claims that lead to detriment for end users. Excessive claims are excessive statements about product efficacy that are not in line with empirical facts, so they can distort the perception of end users and cause financial and psychological losses, as well as potentially threatening health conditions. This scientific study aims to analytically examine the legal accountability of skincare business subjects for end-user losses as a consequence of product excessive claims, specifically within the realm of health and consumer protection legislation (UUPK). Through in-depth interviews with end users, business subjects, and legal experts, this empirical study collects factual empirical data at the research location. Next, the data is analyzed analytically to identify how the implementation of excessive claims and legal accountability is carried out. The study findings indicate that cosmetic businesses that make excessive claims can be subject to administrative and criminal sanctions based on Law Number 8 of 1999 concerning Consumer Protection and the normative technical provisions of the Food and Drug Supervisory Agency (BPOM), and have potential implications for violating the provisions of the Health Law.